Orbital stability of standing waves for supercritical nls with potential on graphs - Alex Javier Hernandez Ardila (2021)
In this paper, we study the existence and stability of normalized standing waves for the nonlinear Schrödinger equation on a general starlike graph with potentials. Under general assumptions on the graph and the potential, we show the existence of orbitally stable standing waves when the nonlinearity is L2-critical and supercritical.